Effects of neutron irradiation on ophthalmic fundus structure, visual function and the mechanisms underlying these effects in rats. (September 2021) - Feng, Jundong; Zhao, Xida; Luo, Yizhou; Zhou, Hao; Xue, Chunyan; Chen, Yueqin; Luo, Huiyao; Liu, Wenqian
Abstract: Introduction: Space radiation can influence the health of astronauts, and neutron radiation plays a crucial role. We researched the effect of neutron on visual organs of rats, and hope to find the possible mechanism. Materials and methods: We irradiated rats with neutrons. Optical coherence tomography (OCT) and fundus photography (FP) were used to study the morphological changes of visual organs in living rats. Electroretinogram (ERG) and visual evoked potential (VEP) were measured to research the changes in visual function. ITRAO/TMT labeling and high PH reverse separation were used to identify and quantify the differentially expressed proteins (DEPs) in the retina to explore the mechanisms. Protein-protein interaction (PPI) networks were used to screen the key proteins closely related to neutron-induced retinal damage. Results: Irradiated rats developed posterior vitreous detachment (PVD). The vessel density of retina increased. The amplitude of b-wave of dark adaptation ERG was increased, which suggested that bipolar cells and Müller cells in retina might be abnormal. The latency of N2-wave of VEP was prolonged, which suggested that combined with the results of nuclear magnetic resonance (NMR)，the the intracranial pressure (ICP) of rats may be increased. Aquaporin-1, vinculin, Tropomyosin-1 and Myosin light chain kinase may be closely related to the retinal damage by neutron. Conclusion: The morphology and function of visual organs are affected by neutrons. The ERG and VEP analysis would be likely to provide reference for non-destructive detection of retinal damage to astronauts in orbit. Highlights: Neutron irradiation injures the ophthalmic fundus construction of rats. Neutron irradiation influence the visual function of rats. B-wave amplitude of dark adaptation ERG changes after irradiation. Both results of VEP and NMR suggest the neutrons induce the ICP increased in rats. The Aquaporin-1, vinculin, Tropomyosin-1 and Myosin light chain kinase may be closely related to retinal damage by neutron.